The benefits mentioned by Imam al-Nawawi in his commentary on Sahih Muslim (The Book of Prayer as a Model) – A Comparative Jurisprudential Study – (College of Basic Education Research Journal, 2025)
Praise be to God Almighty, in this research,  benefits mentioned by Imam Al-Nawawi in his explanation of Sahih Muslim ( Book of Prayer as a Model) - a comparative jurisprudential study - were studied.  In all jurisprudential matters, researcher relied on a lot of  sources and references, and compared  opinions of  jurists of  four schools Hanafi, Maliki, Shafi’i and Hanbali in terms of disagreement and  agreement, ,  weighting their opinions in which there was no agreement from a jurisprudential justification.  Researcher documented  significance of  reasonable doubt.